Light festivals: Entertainment or urban renewal tool?. Issue 1 (1st November 2022) - Bhatia, M
Abstract: This paper is part of the author's thesis wherein she attempted to investigate the hypothesis that a light festival is not only an entertainment based light show but could also be a sustainable renewal strategy for dead urban spaces. 'Public space is our open-air living room' [1], where people meet, interact and replenish their body and mind away from work and home. However, due to various reasons, the current pandemic being one of them, has led to the present generation being seen as an indoor generation [2]. As a result, while a lot of urban spaces are tending to be 'abandoned and left areas that have lost their function' [3]. The author's thesis is a qualitative study to check the feasibility of light festivals as a sustainable strategy to tackle the lifelessness of such dead urban spaces. This paper in particular, presents a qualitative case study of 4 light festivals. This was achieved through both primary sources in the form of personal interviews with organisers and systematic online desk study of the secondary sources of information available as reports by various national and international agencies, journals and peer reviewed papers published by researchers in various online journals of lighting and architecture. These festivals were chosen on the basis of their initial intentions of inception to match the impetus for this study. The success of the festivals is studied with respect to achievement of initial objectives. These are then qualitatively analysed under the categories of image regeneration, revenue generation and job generation to assess the holistic impact of light festivals at various locations in the world. The results of the study suggest that light festivals add playfulness and a sense of identity to public urban scape. The interventions, being temporary in nature, may disappear, but the memory of the event remains in collective memory. Through this, light festivals could potentially transform the views of inhabitants, so that they in turn, can transform their public spaces. The study also suggests that light festivals can be be socially and economically profitable. In conclusion, a light festival could be a successful contender as a sustainable urban renewal strategy.